A review of jet impingement cooling. (February 2023) - Plant, Robert D.; Friedman, Jacob; Saghir, M. Ziad
Abstract: The following work is presented as a review of the different methods used in jet impingement, the aim of which is to improve the heat transfer experienced in each area or volume. Some common applications of jet impingement are metal quenching and electronic cooling. While there is a large difference in the anticipated temperatures of each, the underlying principles are the same. Those principals, summarized in this work, are the improvement of heat transfer in the workspace, which is a much-desired outcome. Some of the common augmentations of jet sprays in this work are nanofluid inclusion, synthetic jets, jet arrays, and vortex jets, with each of which can present their own improvements and detriments. There are often other apparatus that are used in conjunction with a jet spray to help characterize the spray behavior. Some of the methods used are high speed photography and particle velocimetry, which are reviewed in this work as well.